Konsep Good Governance dalam Pandangan Al-Ghazali - Uup Gufron (Direktorat Jenderal Bimbingan Masyarakat Islam, 2015)
Abstract This article focuses on studying and observing the thought of Al-Ghazali on the concept of good governance. It is expected to obtain the answer how exactly the concept of political ethics he put it, so it can be a reference and a foothold in the management of state and government in this modern century. So, this reseach is to answer how the concept of political ethics in the view of of Al-Ghazali and what the view of Al-Ghazali on government ethics that can be interpreted as the principles of good governance is. The objectives of this writing is to make formulation the concept of good governance of Al-Ghazali based on ethics philosophy. The writer concludes that Al-Ghazali suggested or gave some advices to the rulers how to make good governance (husn al-siyâsah) based on ethics. These are formulated into seven principles such as competence (kafă’ah); doing fairness (‘âdalah); live by low profile (basâthah); working honesty (amanâh); having responsiveness (istijăbah); humble and sincerity (Tawaddhu’ wal Ikhlash); and meekness to public (rifq). Abstraksi Tulisan ini fokus pada kajian dan menggali pemikirian Al-Ghazali tentang konsep kepemerintahan yang baik. Diharapkan dapat memberikan jawaban bagaimana sebenarnya konsep etika politik yang ia kemukakan, sehingga dapat menjadi acuan dan pijakan dalam pengelolaan negara dan pemerintahan di abad modern ini. Jadi, penelitian ini adalah untuk menjawab bagaimana konsep etika politik dalam pandangan Al-Ghazali dan apa pandangan Al-Ghazali tentang etika pemerintahan yang dapat diartikan sebagai prinsip-prinsip tata kelola yang baik. Tujuan dari tulisan ini adalah untuk membuat formulasi konsep tata kelola yang baik dari Al-Ghazali berdasarkan etika filsafat. Penulis menyimpulkan bahwa Al-Ghazali menyarankan atau memberikan beberapa nasihat kepada penguasa bagaimana membuat tata pemerintahan yang baik (husn al-siyasah) berdasarkan etika. Ini diformulasikan ke dalam tujuh prinsip seperti kompetensi (kafa'ah); melakukan keadilan ('adalah); hidup dengan rendah hati (basâthah); kejujuran bekerja (amanah); memiliki respon (istijăbah); rendah hati dan ketulusan (Tawaddhu 'wal Ikhlash); dan kelembutan untuk umum (rifq). Keywords: Islam, Government, Good governance